Comprehending words in context : a reaction-time study of lexical ambiguity resolution - Tan, Samuel Wei Jian (2017)
Psycholinguistic research on semantic processing commonly distinguishes bottom-up lexical processes – involving the automatic retrieval of word senses stored in memory – from top-down contextual processes – involving the active imposition of situational constraints on the construal of lexical items (e.g. Andrews & Bond 2009). Extensive studies, since the 1970s, have sought to ascertain whether these two processes are largely autonomous mechanisms or interlinked sub-processes of a single mechanism. This has led to the proposal of three influential models of word processing – namely, the DIRECT ACCESS MODEL, the AUTONOMOUS ACCESS MODEL, and the REORDERED ACCESS MODEL – which critically differ in the extent to which they consider these two processes as largely interrelated or independent. Most recently, two studies (Peleg et al. 2001; 2008) claimed to have found compelling evidence disconfirming the DIRECT ACCESS MODEL and supporting the AUTONOMOUS ACCESS MODEL. The current study suggests theoretical and experimental reasons to doubt the above conclusion, and presents the results of counter-experiments which challenge the AUTONOMOUS ACCESS MODEL and support the REORDERED ACCESS MODEL instead.